Molecular mapping of leaf rust resistance gene in wheat line 19HRWSN-76 - Liusha, Han; Zaifeng, Li; Jiazhen, Wang; Lingzhi, Shi; Lin, Zhu; Xing, Li; Daqun, Liu (The Indian Journal of Genetics and Plant Breeding, 2016)
A highly leaf rust resistant genetic stock 19HRWSN-76 from CIMMYT was crossed to a susceptible variety Zhengzhou 5389 to generate F1 and F2 population to find out the mode of inheritance and map the resistance gene. The F2 population was inoculated with uredosporic inoculum of physiological race FHJP of leaf rust. The 3:1 ratio of resistant and susceptible plants in F2 suggested that the leaf rust resistance in 19HRWSN-76 is controlled by a single gene, tentatively named Lr19HRWSN-76. Relationship between the known leaf rust resistance gene Lr24 and Lr19HRWSN- 76 located on chromosome 3D was established by SSR marker barc71 and STS 24-16